Mistikisme dan Alquran: Makna Simbolik Penyembuhan Kesurupan pada Kesenian Kubrosiswo Bintang Mudo - Hasan, Farid (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2019)
The article addresses the tranced healing phenomena by locating it as a symbolic manifestation of culture that is related to the mystical symbolism and the Qur’an. The research aims to answer the question of what is the meaning of the tranced healing phenomena in the Kubrosiswo Bintang Mudo art show in its mystical symbolism context? By using qualitative method and semiotic approach, I argue that tranced healing phenomena is perceived as encountering two sources of strength, the black power which is coming from Satan, and the holy power which is coming from God. The success of healing the possessed people by using the verses of the Qur’an means a symbolic form of the power of the ba>til which is occupied by the rightly (haqq) power. This affirms a dominative power of God, because humans as ordinary people in their weaknesses of their physical body, when devoting unto God, then it is believed that there is no malevolent strength which is able to impair. In other words, healing is a symbolic manifestation of the nobility of human’s faith unto God.